Instructional Humor in Classroom Contexts: Pragmatic Use and Strategies - Hawraa Jabbar Rahi (مجلة الباحث, 2025)
This study explores the use of instructional humor in classroom contexts, highlighting its usefulness, use, and strategies for implementation. Instructional humor is mainly selected due to its importance as an effective pedagogical instrument that can improve learning experience, foster positive teacher-student relationship, and enhance classroom engagement. Nevertheless, it has not been given an adequate consideration by researchers, as far as the researcher could inspect. This study, hence, is an attempt to achieve the following aims: detecting the criteria that pragmatically best indicate instructional humor in classroom contexts; and identifying the pragmatic strategies used to reflect instructional humor. In line with its aims, this study hypothesizes that: instructional humor is characterized by the availability of various criteria like contextual appropriateness, cultural sensitivity and inclusivity, engagement and motivation, power dynamics and teacher-student relationships, and others; the pragmatic strategies of analogy, hyperbole, exaggeration, mitigating face-threatening acts, codes-switching, personification, simile, and lighthearted self-disclosure can be used by instructors to activate instructional humor. The present study ends up with a variety of conclusions, the most dominant of which is that instructional humor fosters a positive learning environment, improves student-instructor rapport, and facilitates a better understanding of the subject matter